Lietuvos ir Lenkijos konflikto 1918-1920 metais kariniai aspektai - Lesčius, Vytautas (Lietuvos istorijos studijos, 2001)
After restoration of independence in 1918 the Lithuanian state from the very beginning of its activities had to defend the recognition of its very existence and territory by means of both diplomatic measures and armed struggle. One of the neighbouring states, which were encroaching on the independence of the nation, was Poland.  The Poles from ancient times had not shown a favourable view toward the Lithuanian national movement, which they saw only as a certain separatism, and the Poles had been living with ideas of a union that had been unacceptable to Lithuanians for ages.  In Polish eastern policy all their principal political groups assigned Vilnius a special place, which was to be one of the main points of support in creating a "great Poland". Later their aspirations to add all of ethnographic Lithuania became clear. In company with these aims, the opposing actions for the national aspirations of the Lithuanians ignited the spark of the military conflict between the two states.  At the end of 1918 in Vilnius and its environs, the Poles founded a number of soldiers' organisations and self-defence units. Taking advantage of the German army's withdrawal and the relocation of the Temporary Government of Lithuania to Kaunas, they proclaimed the occupation of Vilnius on 01 January 1919. Vilnius remained in their hands for only 5 days this time since they were unable to resist the onslaught on the city by the Bolsheviks.  Having not renounced their idea to repeat military actions, the Poles, taking advantage of a favourable situation, by a sudden assault on 19-21 April 1919, beat the Bolsheviks and drove them out of Vilnius. In governing the city until 14 July 1920, they not only had no consideration for the position of the Lithuanian Government but also persistently infiltrated further into the country, occupying a greater area.  In the middle of June 1920, while the martial activity between Soviet Russia and Poland was tending to the disadvantage of the latter, the hope of getting back their capital Vilnius was ignited for the Lithuanians. The peace treaty between Soviet Russia and Lithuania concluded in Moscow on 12 July, on the basis of which Vilnius and its area together with Suvalkia and Gardinas were recognised as belonging to Lithuania, especially strengthened this hope.  With the Poles withdrawing, the Lithuanian Army on 07 July 1920 began to occupy the localities they had abandoned. On 15 July a part of the Lithuanian Army advanced into Vilnius, and by the end of August had liberated southern Suvalkia. However, the Lithuanian Army faced a serious defeat, and in a large force on 28 August, the small Lithuanian Army units did not attempt to resist. A number of important places were lost and large losses experienced. The Polish-Lithuanian war ended on 07 October 1920 with a treaty signed in Suvalkia.  However, the next day by order of the Polish leader J. Pilsudskis, Gen. L. Želigovskis, as if implementing the will of the "border's" inhabitants, broke the aforementioned treaty and occupied Vilnius. The lingering war ended by the end of November with the route of Želigovskis's soldiers near Širvintos, Giedraičiai, Musninkai. Military actions ended on 01 December.  The Poles did not succeed in implementing their aim of union. The young Lithuanian Army, just being formed, had defended the country's independence.